Nanoceria as a DNase I mimicking nanozyme. Issue 88 (2nd October 2019) - Xu, Fang; Lu, Qinwei; Huang, Po-Jung Jimmy; Liu, Juewen
Abstract : Nanoceria mimics DNase I activity by hydrolytically cleaving DNA down to around 5-mer fragments, demonstrating adsorption, reaction and desorption mechanisms typical of heterogeneous catalysts. Abstract : We herein communicate the DNase I like activity of nanoceria (CeO2 nanoparticles). Both CeO2 and DNase I cleave polyadenine (poly-A) DNA down to ∼5-mer fragments as the major products, although further cleavage to even shorter fragments was observed with CeO2 . Mass spectrometry indicates a hydrolytic cleavage mechanism instead of oxidative cleavage.